Improving Student Motivation and Learning Outcomes on the Material of Mandatory Attributes for God through Learning Videos and Presentations - Laili Alhidayati (MANDAILING GLOBAL EDUKASIA, 2025)
This research is a Classroom Action Research (CAR) which aims to improve students' motivation and learning outcomes in the material of Mandatory Attributes for Allah through the use of learning video media and presentations. The background of this research is the low motivation and learning outcomes of students in the Akidah Akhlak lesson due to monotonous and less interactive learning methods. The research was conducted in class VII MTs Raudhatul Aulia with 16 students in the odd semester of the 2022/2023 school year. The method used in this study refers to the Kemmis and McTaggart model which includes planning, action, observation, and reflection in two cycles.In the initial conditions, only 6 out of 16 students achieved learning completion. After the action in cycle I, the number of students who completed increased to 8 students, and in cycle II it reached 14 students. The results of the analysis showed a significant increase in student activity from 43% in the pre-cycle stage to 93.75% in cycle II. Likewise, the average value of student learning outcomes increased from 51.8 in the pre-cycle to 87.5 in cycle II. The use of learning videos and presentations has been proven to increase student motivation, participation, and understanding of the material. Thus, learning strategies based on visual media and interactive activities such as group presentations are effective in creating a more interesting and meaningful learning atmosphere. This study recommends the application of similar methods in other learning to improve the quality of education.